Exploring Indonesian EFL Pre-Service Teachers’ Professional Identity: Why should be Civil Servant? - Benni Ichsanda Rahman Hz (Journal of English Language Studies, 2024)
This study was conducted to examine the professional identity of EFL (English as a Foreign Language) pre-service teachers in Indonesia after the government announced that no new public servants would be accepted for lecturer and teacher positions starting in 2022. The study involved 153 students from an English language education program at a public university in North Sumatra province. Data was collected through closed-ended questionnaires and semi-structured interviews. The information was analyzed using statistical methods for quantitative data and content analysis for qualitative data. The findings revealed that 48% of the respondents had chosen to become civil servant teachers, and 76.60% of those intending to be civil servant teachers preferred to work as Government Employees with Work Agreements (PPKK) teachers in the future. Numerous rationales and suggestions to remain being professional teachers are then discussed and established.